2016
DOI: 10.3389/fonc.2016.00137
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Individual Radiosensitivity to γ-Rays and Carbon Ions

Abstract: Carbon ions are an up-and-coming ion species, currently being used in charged particle radiotherapy. As it is well established that there are considerable interindividual differences in radiosensitivity in the general population that can significantly influence clinical outcomes of radiotherapy, we evaluate the degree of these differences in the context of carbon ion therapy compared with conventional radiotherapy. In this study, we evaluate individual radiosensitivity following exposure to carbon-13 ions or γ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Therefore, it is necessary to obtain the background frequency for the Tr analysis based on the method of analysis. Furthermore, Shin et al reported a difference in radiosensitivity between healthy individuals [ 32 ], suggesting it might be necessary to adjust the dose estimation by factors other than age.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to obtain the background frequency for the Tr analysis based on the method of analysis. Furthermore, Shin et al reported a difference in radiosensitivity between healthy individuals [ 32 ], suggesting it might be necessary to adjust the dose estimation by factors other than age.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy is a crucial and cost-effective lung cancer curative treatment [ 1 ], and its curative effect largely depends on the radiosensitivity of tumor cells of the different patients [ 2 ]. So, the valuation of radiosensitivity with respect to radiotherapy has significant potential to contribute to further therapeutic gain.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are membrane-bound extracellular vesicles (50–150 nm) which are released by cells into the extracellular environment [ 20 ]. These are known to have an important role in the intercellular communication, such as tissue repair and the immune system, influencing cell phenotype as well as the nervous system [ 21 ]. The released exosomes interact with target cells through expressed growth factors, bioactive lipids and membrane receptors, which could cause a direct stimulation for the target cells [ 22 ].…”
Section: Introductionmentioning
confidence: 99%